QUANTUM-CHEMICAL SIMULATION OF COPPER OXIDE NANOPARTICLES STABILIZATIO - D. M. Remizov; A. A. Gvozdenko; A. V. Blinov; V. V. Raffa; A. B. Golik; D. G. Maglakelidze; A. A. Blinova (Современная наука и инновации, 2022)
The article presents the results of quantum-chemical simulation of the copper oxide nanoparticles stabilization process with various stabilizers. The simulation was carried out using the QChem software and the IQmol molecular editor. Quantum-chemical models of CuO-stabilizer molecular systems were obtained. Hydroxymethylcellulose, hydroxyethylcellulose, cetyltrimethylammonium bromide, polyvinylpyrrolidone, chitosan, and hyaluronic acid were used as stabilizers. Analysis of the data obtained showed that the most energetically favorable (E = -3557, 94 kcal/mol) and stable (AE = 0.260 eV) molecular system was the "CuO-hyaluronic acid" system.